Synthesis and Crystal Structures of Some Pyridyl Aminothiazole and Thiazolidin-2-ylidene Benzamide Derivatives - Heydari, Reza; Shahrekipour, Fahimeh; Graiff, Claudia (Letters in Organic Chemistry, 2016)
Background: Thiazoles and their derivatives are attracting continuing interest over the years because of their varied biological activities. Thiazole and in particular the 2-amino thiazole moiety has been incorporated into a wide variety of therapeutically interesting candidates including antibacterial, anti-HIV, hypertension, anti-inflamenmatory, anti-viral and anticancer agents. Methods: Several methods for the synthesis of thiazole derivatives have been developed. The most widely used method being the Hantzch’s synthesis. In this paper, we describe an efficient one-pot method for the synthesis of some thiazolidin-2-ylidene benzamide and aminothiazole derivatives via condensation of 3-aminopyridine or 2- aminopyridine with phenacyl bromide and benzoyl isothiocyanates. Results: The reaction of 3-aminopyridine, benzoyl isothiocyanates, and phenacyl bromide in the presence of triethylamine yields thiazolidin-2-ylidene benzamides, which upon heating in acetic acid produce pyridyl aminothiazole derivatives. Also the pyridyl aminothiazole derivatives were obtained by the reaction of 2-aminopyridine with benzoyl isothiocyanates and phenacyl bromide in the presence of triethylamine. The molecular structures of the 4-chloro-N-(4-hydroxy-4-phenyl- 3-(pyridin-3-yl)thiazolidin-2-ylidene)benzamide, phenyl(4-phenyl-2-(pyridin-3-ylamino)thiazol-5-yl)methanone and (4- phenyl-2-(pyridin-2-yl amino)thiazol-5-yl)(o-tolyl)methanone, have been fully determined by means of single crystal Xray diffraction methods. Conclusion: In summary, present study reports one-pot synthesis of thiazolidin-2-ylidene substituted benzamide and pyridyl aminothiazole derivatives via condensation of 3-aminopyridine or 2-aminopyridine with phenacyl bromide and substituted benzoyl isothiocyanates. The single crystal X-Ray diffraction analysis reveals unequivocally the exact identity of the compounds.
Keywords: 3-aminopyridine